Transdisciplinary Approaches To Developing A Mice Tourism Model Based On Local Cultural Heritage: A Case Study Of Binh Duong - Tran Hanh Minh, Phuong (Journal of Entrepreneurship & Business, 2025)
Purpose: This study aims to develop a culturally grounded Meetings, Incentives, Conferences, and Exhibitions (MICE) tourism model for Thanh Hoi and Bach Dang islands in Binh Duong, Vietnam. Although both islands possess rich tangible and intangible heritage—from archaeological sites and ancient communal houses to pomelo orchards and wartime narratives—they have yet to feature in formal tourism circuits. The novelty lies in employing a transdisciplinary co-design approach, involving academic researchers, local residents, cultural officers, and tourism businesses. Method: The study employed Participatory Rural Appraisal (PRA) workshops with community members, semi-structured interviews with 35 stakeholders (including local authorities and tourism providers), and field observations. The conceptual framework integrated systems knowledge, target knowledge, and transformation knowledge, analyzed using thematic coding and comparative stakeholder analysis. Result: Key findings reveal that while the islands have high cultural tourism potential, development is hindered by infrastructure gaps (internet, event venues), fragmented branding, and limited service capacity. Stakeholders proposed innovative MICE products—such as agro-heritage retreats and river-ecology workshops. The study concludes that a stakeholder-driven, heritage-based MICE model can position these rural islands as distinctive destinations. Future research should test the model’s scalability in similar riverine heritage sites across Southeast Asia.